(untitled) (Praxis Educativa, 2023)
Latin American critical pedagogies seek to train subjects capable of understanding and transforming their social realities, with more democratic and equitable political horizons. Decolonial feminism, for its part, analyzes the historical configuration of colonized societies, which have become modern, capitalist and patriarchal. This essay aims to find meeting points between critical pedagogies and decolonial feminism, especially considering the contributions of Rita Segato. Her notions of "mandate of masculinity" and "pedagogy of cruelty" reveal social processes of naturalization of a growing violence against women, which impact on the whole of social life. Knowing the consequences of the pedagogy of cruelty for the social bond is key to the perspective of critical pedagogies, at a historical moment in which a change of era seems to be approaching and it is essential to sustain the democratic agreements achieved to date.